Efektivitas Delignifikasi Limbah Mesokarp Kelapa Sawit untuk Meningkatkan Potensi Selulosa - Yuniar, Rizka Ayu; Purwati, Esty; Samudera, Borneo Bayu; Hidayat, Jefri Pandu (Jurnal Serambi Engineering, 2025)
Biomass-based products are increasingly being used in industrial applications, but these innovations require efficient pretreatment to standardise the raw materials. In this study, the characteristics of oil palm mesocarp fibres after alkali processing were evaluated. The process consisted of two stages: delignification and bleaching. The organosolv extraction method was used to increase the efficiency of delignification during the bleaching stage. The mesocarp fibres were analysed using the kappa number test, scanning electron microscopy and Fourier transform infrared spectroscopy. A decrease in kappa number was observed, indicating a lower lignin content in the mesocarp samples. The FTIR spectrum showed a decrease in the peak intensity of C=C bonds in lignin at wavelengths of 1400-1500 cm-¹. Structural changes in fibre morphology after delignification and bleaching were observed, indicating that lignin had been successfully extracted from the mesocarp fibres. Optimal conditions for kappa number reduction were obtained at a NaOH concentration of 1 M, a delignification time of 4 h and a NaOCl volume of 280 ml (28 ml/g).